Betrayal - Stockwin, Julian (Stockwin, Julian. Kydd series, 2012)
Cape Colony is proving a tiresome assignment for Thomas Kydd's daring commander-in-chief Commodore Popham: South America's Spanish colonies are in a ferment of popular unrest. Rumors of a treasure hoard of Spanish silver spur him to assemble a makeshift invasion fleet and launch a bold attack on the capital of the Viceroyalty of the River Plate in Buenos Aires. Navigating the treacherous bars and mud flats of the river, the British invasion force wins a battle against improbable odds, taking the capital and the silver. But the uprising that promises the end of Spanish rule never arrives and the locals begin to see dark conspiracies behind the invader's actions. Now Kydd's men must face resistance and the betrayal of their closest allies. Can they save themselves and their prize?